Faculty-student perceptions about entrepreneurship in six countries. Issue 1 (9th January 2017) - Pruett, Mark; Şeşen, Harun
Abstract : Purpose: In what may be the first study of its kind in business and entrepreneurship, the purpose of this paper is to compare faculty and student perceptions and beliefs about entrepreneurship motives and barriers and student aspirations in order to explore implications for entrepreneurship education (EE). Design/methodology/approach: The authors survey 3, 037 students and faculty in the USA, China, India, Turkey, Belgium, and Spain, focusing on perceptions of entrepreneurship motives and barriers. Factor analysis organizes data for comparisons and regressions. Findings: The authors find significant faculty-student differences in views of entrepreneurship motives and barriers, university environments, and student aspirations. An especially important finding is that, across six countries with widely varying cultures, economies, and entrepreneurial environments, students consistently see themselves as more entrepreneurial than the faculty perceive. Research limitations/implications: Limitations include sample size and self-reporting. The authors also have focused on the significance of differences in perceptions, not on whether faculty or student perceptions are correct. A major implication of the study is that EE curricula need to be assessed in terms of their impact on the self-confidence, risk aversion, and entrepreneurial disposition of students. Originality/value: The authors shine light on an overlooked topic – faculty-student perceptual alignment – to stimulate research and strengthen EE, especially regarding students' self-confidence and views of failure and risk.